Analisis Efektivitas Konten Video Promosi di Media Sosial Instagram pada UMKM Kaikaiqu Dua Puteri Kabupaten Malang - Silka Putrismi; Dwi Sudjanarti; Heru Utomo (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
Instagram has become one of the digital promotional media widely used by micro, small, and medium enterprises (MSMEs). However, the promotional video content of Kaikaiqu Dua Puteri MSME in Malang Regency has not effectively attracted audience attention or increased audience engagement. This study aims to analyze the existing promotional video content, design more effective promotional video content, and evaluate the effectiveness of promotional video content on the Instagram account of Kaikaiqu Dua Puteri MSME. This study employed an action research method with a descriptive qualitative approach conducted through two cycles: planning, acting, observing, and reflecting. All EPIC Model dimensions in Cycle II achieved the Very Effective category with mean scores ranging from 4.75 to 4.90, while the engagement rate reached 6.2%, classified as Very High. These findings indicate that improvements in the script, visuals, audio, call-to-action, and legal information increased audience engagement with the promotional content. This study concludes that the Instagram promotional video content developed for Kaikaiqu Dua Puteri MSME was proven to be effective based on the EPIC Model and engagement rate measurements, thereby providing a reference for MSMEs in developing effective digital promotional conten.